2015
DOI: 10.5539/ijbm.v10n3p57
|View full text |Cite
|
Sign up to set email alerts
|

Can Z-Score Model Predict Listed Companies’ Failures in Italy? An Empirical Test

Abstract: The Altman Z-score model for predicting bankruptcy of businesses was constructed and fine-tuned in the USA in 1968 and updated in 1999. It is therefore possible that its results cannot be extended to non-Anglo-Saxon countries in today's context. This paper ascertains if the Z-score can correctly predict the failure of industrial listed companies in Italy. First, we have analyzed the theoretical and practical characteristics of the original Z-score model and we highlight some of its potential shortcomings. Seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 27 publications
(20 reference statements)
2
19
0
7
Order By: Relevance
“…It was concluded that original Z-score model performs well in an international context and its classification accuracy can be enhanced by introducing additional variables. Celli (2015) verified the distress prediction power of original Z-score model and it was found that Z-score model has high predictive power as shown by overall successful rate 87.3%, 77.5% and 66.6% before one, two and three years of default. It was concluded that Z-score model can predict distress with high level of accuracy and low error rate.…”
Section: Reveiw Of Literaturementioning
confidence: 58%
See 1 more Smart Citation
“…It was concluded that original Z-score model performs well in an international context and its classification accuracy can be enhanced by introducing additional variables. Celli (2015) verified the distress prediction power of original Z-score model and it was found that Z-score model has high predictive power as shown by overall successful rate 87.3%, 77.5% and 66.6% before one, two and three years of default. It was concluded that Z-score model can predict distress with high level of accuracy and low error rate.…”
Section: Reveiw Of Literaturementioning
confidence: 58%
“…After the development of the Altman's model many authors or researchers developed their own models by using different variables and methodology. Many studies like Agarwal and Taffler (2005), Sarbapriya (2011), Rayalaseema and Muhammad (2012), Anjum (2012), Karamzadeh (2013), Altman et al (2014), Celli (2015) etc. tested the predictive accuracy of the Altman's model by applying it to the recent time period and it was found that Altman's model is still a powerful tool to predict the bankruptcy.…”
Section: Introductionmentioning
confidence: 99%
“…En el ámbito latinoamericano, se ha empleado el modelo original ajustado a las características específicas de países como Costa Rica (Vargas, 2013) o Colombia (Berrío y Cabeza, 2015). En Europa se ha aplicado el modelo a las empresas italianas (Altman et al, 2015;Celli, 2015) y a las griegas (Gerantonis et al, 2009), mientras que en Asia ha sido empleado a las compañías chinas (Thomas et al, 2011) entre otras.…”
Section: La Quiebra: Concepto Y Predicciónunclassified
“…According to the results, Zmijewski followed by Springate and Altman model gives high accuracy in bankruptcy prediction rate that leads to delisting. Celli (2015) examined a data of 102 Italian companies listed at Italian stock exchange for a period of 1995-2013 using Altman Z-score. From these 102 companies there were 51 companies were delisted and 51 were listed.…”
Section: Empirical Studies5mentioning
confidence: 99%